In memoriam : Frederick Sanger (1918-2013) - Singh, Vivek (International Journal of Applied Sciences and Biotechnology, 2013)
No abstract DOI: http://dx.doi.org/10.3126/ijasbt.v1i4.9313 Int J Appl Sci Biotechnol, Vol. 1(4): 158-161